Trade and development - BURKHANOV, Akhror (KDI School, 2016)
As globalization spawned all over the world absorbing more and more countries in its economic net, many scholars in the field of economics have focused on the analysis of international trade and development from different angles. The relationship of trade and economic growth has been receiving increasing attention from governments and researchers. Many suggest different degrees of statistical correlation results between these variables ranging from weak to strong. However, there is more than one way of addressing the question of development and trade; it is obvious that development fastens with increased engagement in to the global economy through international trade. Number of developing countries including one of the two double landlocked countries, Uzbekistan, is trying to utilize the lessons from successes and failures of globalizing world economy to their benefit. There are many challenges and possible solutions in strengthening sustainable capacity of developing Uzbekistan in becoming export oriented economy
Thesis(Master) --KDI School:Master of Development Policy,2016